2011
DOI: 10.1155/2011/490634
|View full text |Cite
|
Sign up to set email alerts
|

Help Seeking and Access to Primary Care for People from “Hard-to-Reach” Groups with Common Mental Health Problems

Abstract: Background. In the UK, most people with mental health problems are managed in primary care. However, many individuals in need of help are not able to access care, either because it is not available, or because the individual's interaction with care-givers deters or diverts help-seeking. Aims. To understand the experience of seeking care for distress from the perspective of potential patients from “hard-to-reach” groups. Methods. A qualitative study using semi-structured interviews, analysed using a thematic fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 28 publications
1
46
0
1
Order By: Relevance
“…Of equal importance is the preference of many to recommend help-seeking from GPs. Primary care providers are often the first point of contact for many people with mental illness (Bristow et al, 2011) and they can also act as gatekeepers to other services.…”
mentioning
confidence: 99%
“…Of equal importance is the preference of many to recommend help-seeking from GPs. Primary care providers are often the first point of contact for many people with mental illness (Bristow et al, 2011) and they can also act as gatekeepers to other services.…”
mentioning
confidence: 99%
“…It contributes to a growing body of research emphasising the social processes of help-seeking, and the expertise patients bring to decision-making around health-care use. 286,287 When patients with LTCs feel vulnerable in health crises, it is their previous experience of services that shapes their perception of candidacy and thus their choice of service to access, with patterns of under-or over-use of services becoming established recursively based on these responses. This is consistent with the ACMs and SNs who described making their systems permeable so that patients used them instead of unscheduled care.…”
Section: Use Of Unscheduled Care: Perspectives Of Patients and Healthmentioning
confidence: 99%
“…Most older people manage their feelings of distress on their own and do not seek help from healthcare services 10 . This could be because older adults do not recognise distress as a biomedical problem and do not view biomedical treatments as appropriate 11 . Through exploring lay perspectives on the solutions offered by GPs to patients experiencing distress, Geraghty et al 12 reported that GPs primarily offered reassurance, time off work or medication to help them to sleep.…”
Section: Introductionmentioning
confidence: 99%